2011
DOI: 10.1111/j.1551-2916.2011.04404.x
|View full text |Cite
|
Sign up to set email alerts
|

Porous Biphasic Calcium Phosphate Scaffolds from Cuttlefish Bone

Abstract: Cuttlefish bone is an inexpensive, readily available, morphologically complex natural material. It has an open structure, consisting of layers separated by pillar-like structures made of calcium carbonate. In this study natural bones from cuttlefish were successfully converted into porous biphasic calcium phosphate (BCP) scaffolds with a range of hydroxyapatite and b-tricalcium phosphate compositions. The process involved reaction with solutions of phosphoric acid (H 3 PO 4 ) and 2-propanol, followed by heat t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 42 publications
1
41
0
1
Order By: Relevance
“…Sarin et al 21 have reported that CB was converted into biphasic calcium phosphate (BCP) by the hydrothermal conversion method, and could retain its porous structure after conversion. According to their report, the compressive strength of raw CB was slightly decreased after conversion into BCP from 2.38 to 2.19 MPa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sarin et al 21 have reported that CB was converted into biphasic calcium phosphate (BCP) by the hydrothermal conversion method, and could retain its porous structure after conversion. According to their report, the compressive strength of raw CB was slightly decreased after conversion into BCP from 2.38 to 2.19 MPa.…”
Section: Discussionmentioning
confidence: 99%
“…This decrease in compressive strength may be due to the removal of the organic framework of b-chitin by heating during the hydrothermal reaction. 21 In the present study, to improve the compressive strength, CB-HAp was coated by the simple dipping-and-drying method using several concentrations of PCL. The results show that the compressive strength was increased by coating with 5 and 10% PCL.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the requirement for a specific macroporosity of the ceramic scaffold, a certain percentage of microporosity is important for osteogenesis and the anchoring of the implant to sur rounding bone tissue [14]. Therefore, several techniques were developed to integrate the desired porous structure into calcium phosphate scaffolds [15][16][17][18][19][20][21][22][23][24][25][26]. One of these techniques is to coat polymeric sponges with a ceramic slurry.…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, the infiltration of the solution into the CB occurred under vacuum conditions and for 1 h. This process was followed by heat treatment at high temperatures, up to 1300°C. The BCP scaffolds obtained with 16 wt% of phosphoric acid preserved the initial microstructure of CB and exhibited a compressive strength of 2.38 ± 0.24 MPa that despite being lower than the raw CB (2.74 ± 0.39 MPa), is in the range of trabecular bone [196]. Dutta et al [197] produced the CaP scaffolds derived from CB in ambient conditions using a de-calcification, re-calcification process followed by a phosphate mineralization.…”
Section: Cuttlefish Bonementioning
confidence: 99%
“…Alternative methods to HT can be used to produce CaP materials derived from CB. For instance, Sarin et alc [196] reported the production of BCP scaffolds from CB using a solution of phosphoric acid and 2-propanol with different concentrations of phosphoric acid from 12 to 20wt%. Briefly, the infiltration of the solution into the CB occurred under vacuum conditions and for 1 h. This process was followed by heat treatment at high temperatures, up to 1300°C.…”
Section: Cuttlefish Bonementioning
confidence: 99%